ANALISIS YURIDIS DISPARITAS PIDANA PADA KASUS PENYERTAAN TINDAK PIDANA KORUPSI PENGADAAN BUKU DI KOTA PADANG PANJANG - Nur Farah Datulaida; Erdianto Erdianto; Davit Rahmadhan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The issue of corruption is a problem that has grown for a very long time and has takenroot in every sector of state life. This crime has damaged the good order in achieving socialwelfare. And the high number of corruption cases in the procurement of goods and services isdue to gaps in regulations that are not yet perfect. A field that accommodates a lot of things mustbe able to provide guarantees that it will provide justice to the parties involved.The type of research used in this legal research is normative juridical method. Therefore,an analysis with a qualitative measure is used which is based on substance with data collectionin drawing conclusions. In drawing conclusions the author uses the deductive thinking method,namely a way of thinking that draws a conclusion from things that are general to things that arespecific.From the results of the research and discussion it can be concluded that, first, theregulation on the procurement of goods and services, which is currently still in the form of apresidential regulation, has resulted in weak law enforcement regarding problems arising fromthe process of procurement of goods and services, including the problem of corruption. Second,that justice is when everyone gets their rights, when there is an act of corruption that takes awaythe right to the needs of the state and people's welfare and the interests of the community, thenjustice has been taken away, for this reason law enforcement and regulatory improvement tostabilize justice in its place is a must. Third, the idea of regulating the procurement of goods andservices in the future to minimize and also prevent criminal acts of corruption in this sector fromrecurring is the presence of laws that specifically regulate the procurement of goods andservices, so that violations of these articles give the power to impose penalties on those whoviolate them.Keyword: Procurement – a criminal act of corruption